Mass spectrometry-based N-glycosylation analysis in kidney disease - Ren, Weifu; Bian, Qi; Cai, Yan (Frontiers in Molecular Biosciences, 2022)
Kidney disease is a global health concern with enormous expense. It is estimated that more than 10% of the population worldwide is affected by kidney disease and millions of patients would progress to death prematurely and unnecessarily. Although creatinine detection and renal biopsy are well-established diagnostic tools for kidney disease, they are limited by several inevitable defects. Therefore, biomarkers and techniques are needed to upgrade, especially for the diagnosis of early stage of the disease and for the prediction of progression. As one of the most common post-translational modifications of proteins, N-glycosylation plays a vital role in renal structure and function. Deepening research on N-glycosylation in kidney disease provides new insights into the pathophysiology and paves the way for clinical application. In this paper, we reviewed the recent N-glycosylation studies on several kidney diseases. We also summarized the development of mass spectrometric methods in the field of N-glycoproteomics and N-glycomics.